Meta-analysis of the association between overexpression of RAD51 family genes and prognosis and clinical features in breast cancer - Yong-Cheng Liu; Jun Shen (Scientific Reports)
Abstract The RAD51 family of genes play a crucial role in the repair of DNA damage, and increasing evidence suggests a close link between the aberrant expression of RAD51 family genes and the development of breast cancer. However, their prognostic and clinical relevance remains subjects of ongoing debate. This study aims to systematically investigate the relationship between the overexpression of RAD51 family genes and breast cancer prognosis, as well as their association with clinicopathological characteristics, through a comprehensive meta-analysis. PubMed, EMBASE, OVID, Web of Science, Scopus, and Cochrane Library were systematically searched for relevant studies published up to August 25, 2024. Two independent researchers screened the literature according to predefined inclusion and exclusion criteria and extracted relevant data. Statistical analyses were conducted using the Meta package in R 4.2.2. Thirteen studies comprising 20,222 breast cancer patients were included. High expression of RAD51 family genes was associated with poorer overall survival (OS) [HR = 1.305, 95%CI (1.145–1.488), P < 0.01], disease-free survival/distant metastasis-free survival (DFS/DMFS) [HR = 1.588, 95%CI (1.208–2.089), P < 0.01], and disease-specific survival (DSS) [HR = 1.403, 95%CI (1.066–1.846), P = 0.02]. In addition, subgroup analyses further showed that high RAD51 expression was associated with worsened OS [HR = 1.475, 95%CI (1.275–1.706), P < 0.01], DFS [HR = 1.584, 95%CI (1.133–2.215), P < 0.01] and progression-free survival (PFS) [HR = 2.439, 95%CI (1.172–5.075), P = 0.02]. In contrast, high expression of RAD51 paralogs was linked to improved PFS prognosis [HR = 0.870, 95%CI (0.797–0.949), P < 0.01]. Regarding clinical characteristics, high expression of RAD51 family genes was significantly associated with human epidermal growth factor receptor 2 (HER2) positivity [OR = 1.782, 95%CI (1.328–2.392), P < 0.01]. The overexpression of RAD51 family genes is correlated with unfavorable prognosis in breast cancer and exhibits a strong association with HER2-positive subtypes. These findings underscore the potential of RAD51 family genes as prognostic biomarker and therapeutic targets in breast cancer management.